Pseudo-aneurysm caused from banding failure. Issue 4 (July 2018) - Mallios, Alexandros; Boura, Benoit; Costanzo, Alessandro; Combes, Myriam
Background: To present a case of banding failure with vessel wall erosion and pseudo-aneurysm creation caused by the suture. Case report: A 75-year-old male patient was operated for a high-flow fistula (>2 L/min). This was overall the third time that the patient was operated for the same indication since he started dialysis 5 years ago. Standard banding technique with perioperative flow measurements was used, and three separate Prolene sutures tied over 5 and 4.5 mm probes to achieve flow reduction. The operation was successful and first few weeks were uneventful. However, 5–6 weeks postoperatively, the patient felt locally an acute pain that lasted only few seconds and a voluminous aneurysm occurred progressively within the next few weeks. He was observed 2 months after the first operation where a recurrent high-flow fistula was diagnosed and ultrasound examination revealed that the sutures used for banding were into the vessel lumen while a pseudo-aneurysm had occurred at the same level. The patient was re-operated for excision of the aneurysm and flow reduction with tapering of the anastomosis. Conclusion: Under certain conditions, the suture used for banding may erode through the vessel wall and get into the lumen. This will result in recurrence of a high-flow fistula. While this has been previously described, the phenomenon was otherwise uneventful. In contrary, in the case presented herein, a potentially threatening pseudo-aneurysm has occurred.